Oncogenic high-risk human papillomavirus detection and evaluation of risk factors in the cervical intraepithelial neoplasia I - Fedrizzi, Edison Natal; Ribeiro, Ângela Fantin; Aguiar, Fabiana Gomes de; Caporal, Fabio Tonon; Sommacal, Luiz Fernando; Gomes, Liliane Raupp (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: The cervical intraepithelial neoplasia grade I (CIN I) shows an important percentual of spontaneous regression (80%) and there is no universal consensus if these lesions should be treated or only monitored. Lesions at risk for progression are precisely those associated with high-risk HPV. Knowing which CIN I are related to these viruses may be one of the determining factors for the decision to treat or not. Objective: To determine the prevalence of high-risk HPV in women with CIN I and to evaluate if there is an association between the presence of the virus and some risk factors. Methods: Cross-sectional descriptive study. We evaluated 55 women with histological diagnosis of CIN I. All of them were previously submitted to HPV-DNA testing. Results: 25 out of 55 (45.5%) women analyzed were positive for high-risk HPV. The virus infection was related with higher level of education, smoking and history of sexually transmitted diseases. Other risk factors like age, number of sexual partners, age at first sexual intercourse, use of hormonal contraceptives, and immunosuppression condition did not show a relation to the high-risk HPV infection. Conclusions: The prevalence of high-risk HPV in women with histological diagnosis of CIN I was 45.5%. HPV-DNA detection was associated with smoking, history of sexually transmitted diseases, and higher level of education.